2021
DOI: 10.7759/cureus.19025
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Ability of Neutrophil-Lymphocyte Ratio in Determining Tumor Staging in Colorectal Cancer

Abstract: IntroductionTumor staging plays an important role in determining treatment in colorectal cancer. In the recent past, the neutrophil-lymphocyte ratio (NLR) has been used as a predictive marker of inflammation for different types of clinical entities. Our study aims to determine if NLR can predict tumor staging in patients with colorectal cancer. Materials and methodsWe retrospectively analyzed all cases that underwent surgical treatment for colorectal cancer from 2014 to 2020. The NLR, tumor stage, and histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…NLR, with a HR of 1.2269 and a significant p -value of 0.0057, suggests a higher NLR could be indicative of a poorer prognosis in CRC, pointing to the potential of NLR as a valuable prognostic marker. These findings are consistent with previous studies that have identified high NLR values as indicators of systemic inflammation and poor prognosis in CRC patients [ 24 , 25 ]. A recent meta-analysis, comprising 32.788 patients, investigated the prognostic utility of pre-treatment NLR for overall survival and progression-, recurrence-, or disease-free survival in CRC patients, claiming that NLR can be fully assessed as an independent predictor of CRC progression and outcome further supporting our finding [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…NLR, with a HR of 1.2269 and a significant p -value of 0.0057, suggests a higher NLR could be indicative of a poorer prognosis in CRC, pointing to the potential of NLR as a valuable prognostic marker. These findings are consistent with previous studies that have identified high NLR values as indicators of systemic inflammation and poor prognosis in CRC patients [ 24 , 25 ]. A recent meta-analysis, comprising 32.788 patients, investigated the prognostic utility of pre-treatment NLR for overall survival and progression-, recurrence-, or disease-free survival in CRC patients, claiming that NLR can be fully assessed as an independent predictor of CRC progression and outcome further supporting our finding [ 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…The prognosis of different stages of CRC varies greatly, whereas early-onset CRC is insidious and failure to be diagnosed. NLR was reported to predict tumor staging in patients with colorectal cancer ( 29 ). The patient population enrolled in each study was different stage and treatment strategies, but most papers analyzed “pre-NLR” in patients with stage II-III colorectal cancer ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a single indicator is greatly affected by physiology and stress, and the detection results have a large fluctuation range and low stability. NLR can stably reflect the relationship between multiple factors and the interaction of inflammatory response, immune system in the body ( 20 ). In this study, CRC staging is positively correlated with NLR.…”
Section: Discussionmentioning
confidence: 99%